1999
DOI: 10.1038/sj.bjc.6690770
|View full text |Cite
|
Sign up to set email alerts
|

The role of endogenous interleukin-2 in proliferation of human carcinoma cell lines

Abstract: Summary Interleukin (IL-2) and IL-2Rβ/γ have been shown to be expressed in human carcinomas in culture and in situ. Recently, expression of endogenous IL-2 and IL-2R in the cytoplasm was found to be up-regulated in tumour cells undergoing mitosis. This observation suggested that similar to its role in lymphocytes, the IL-2/IL-R pathway is involved in the regulation of carcinoma cell proliferation. Metabolic labelling followed by immunoprecipitation and Western blot results showed that IL-2 in carcinomas was id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…However, exogenous IL-2 used at therapeutic doses was found to inhibit carcinoma growth in vitro and in vivo in nude mice (Weidmann et al, 1992;Rabinowich et al, 1992). The opposite biologic e ects of endogenous vs exogenous IL-2 described by us earlier (Reichert et al, 1999) emphasize the complexity of interactions between autocrine and exocrine IL-2 pathways.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…However, exogenous IL-2 used at therapeutic doses was found to inhibit carcinoma growth in vitro and in vivo in nude mice (Weidmann et al, 1992;Rabinowich et al, 1992). The opposite biologic e ects of endogenous vs exogenous IL-2 described by us earlier (Reichert et al, 1999) emphasize the complexity of interactions between autocrine and exocrine IL-2 pathways.…”
Section: Discussionmentioning
confidence: 76%
“…The IL-2/IL-2R pathway in human carcinoma TE Reichert et al growth (Table 2), under conditions described earlier (Reichert et al, 1999). While this strategy indicated that inhibition of endogenous IL-2 resulted in the upregulation of both p27 and p21 CDK inhibitor levels (Figure 8), it also suggested the existence of complex regulatory mechanisms involving this endogenous cytokine IL-2.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Experimental studies of squamous cell carcinomas of head and neck have shown that antisense IL-2 treatment or blocking of IL-2Rβ results in growth inhibition [12]. …”
Section: Introductionmentioning
confidence: 99%
“…Recently, a contrary finding on IL-2 function was reported, in which endogenous IL-2 promoted tumor cells growth and protected these cells from apoptosis [18]. Thus, the role of cytokines produced by cells in the peritoneal cavity in tumor growth in gastric cancer patients is still unclear.…”
Section: Discussionmentioning
confidence: 96%